Mesmerization with the Lights On: Poe’s “The Facts in the Case of M. Valdemar” - Tindol, Robert (Text Matters: A Journal of Literature, Theory and Culture, 2021)
Edgar Allan Poe’s eerie short story “The Facts in the Case of M. Valdemar” is a particularly noteworthy example of the sublime, a psychological state in which one is overwhelmed by the magnitude of that which is perceived by the mind. Valdemar exemplifies the sublime in that his death has somehow been suspended in time because he was under hypnosis as part of a medical experiment at the moment of his passing. However, the story also draws particular attention to the means by which insight into the nature of death is acquired by the hypnotist who narrates the story. For a more comprehensive understanding of the sublime experience, one may turn to the psychoanalytic theory of Jacques Lacan and the postmodernist work of Slavoj Žižek, which lead to the conclusion that the dramatic chain of events in “Valdemar” is an example of the sliding signifier, and, moreover, that the instability of the signifier may explain the sublime effect.